Clay modeling - Speechley, Greta (Chicago, Ill. : Heinemann Library, 2000)
Offers information on materials and techniques for modeling in clay, and suggests a variety of projects, including animals, containers, and a fish tile.
Includes bibliographical references and index.
8 - 10 years
Keywords: Modeling -- Juvenile literature; Clay -- Juvenile literature; Modeling; Clay; Handicraft